Caring for children with SAM: Intersectional stories of shame, blame and stigmatisation in Zimbabwe, Zambia and Kenya - Tim Brown; Kavita Datta; Catherine Achieng; Jacqueline Kabongo; Joseph M. Zulu; Mutsa Bwakura-Dangarembizi; Andrew Prendergast (Global Public Health)
This paper draws from qualitative research undertaken with the mothers and primary caregivers of children aged under 5 years old and in recovery from severe acute malnutrition (SAM), as well as other community members, across three study sites in Kenya, Zambia, and Zimbabwe. The paper highlights how nutrition-related stigma is constructed and enacted in complex ways, by multiple actors and across diverse settings. Adopting an intersectional approach, the paper identifies how stigma emerges at the intersections of social identity, especially age, gender, and associated beliefs about women’s, and especially young women’s, assumed (in)capacity to care. The paper highlights how such stigmatising practices have the potential to place the children of mothers and primary caregivers affected by stigma at heightened vulnerability to SAM as well as to impair their recovery because of its impact upon health-seeking behaviours. In conclusion, we argue that intersectional approaches to stigma are crucial to better understand the social construction of stigma pertaining to SAM, the differential experiences, and responses, of caregivers, as well as how these shape pathways to differing forms of care.